Cytosolic phospholipase A2 links tau pathology to insulin signaling impairment in Alzheimer’s disease - Hossen, Faruk; Hung, Javier; Odeh, Hamza; Sun, Grace Y.; Lee, James C. (Frontiers in Aging Neuroscience, 2025)
Although impaired insulin signaling in the brain has been recognized as a key factor in the development and progression of Alzheimer’s disease (AD), the underlying mechanisms remain incompletely understood. Given that overactivation of cytosolic phospholipase A2 (cPLA2) has been implicated in AD, we tested the hypothesis that oligomeric tau (oTau) activates cPLA2, which in turn negatively affects Caveolin-1 (Cav-1) and insulin signaling. In the cerebral cortex and hippocampus of 12-months-old 3xTg-AD mice, we observed an upregulation of phosphorylated cPLA2 (p-cPLA2), accompanied by downregulation of Cav-1 and impaired insulin signaling. Specifically, we found significant decreases in insulin receptor-α (IR-α) and insulin receptor-β (IR-β) expression, along with increased levels of phospho-insulin receptor substrate 1 at Ser307 [p-IRS-1 (Ser307)] and decreased levels of p-IRS-1 (Tyr895), compared to wild-type (WT) mice. To further investigate the role of cPLA2 in insulin signaling impairment in AD, we demonstrated that oTau activated cPLA2 in primary mouse cerebral endothelial cells (CECs), leading to Cav-1 downregulation and disrupted insulin signaling. Notably, these detrimental effects of oTau on Cav-1 and insulin signaling were abolished when cPLA2 expression was depleted using small interfering RNA (siRNA). In conclusion, our study highlights the pivotal role of cPLA2 in regulating Cav-1 function and insulin signaling in AD, offering insights into potential therapeutic targets for mitigating insulin resistance associated with the disease.